2015
DOI: 10.1016/j.marpol.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Daily variation of fishing effort and ex-vessel prices in a western Mediterranean multi-species fishery: Implications for sustainable management

Abstract: Highlights  Effort variation was due to higher effort at the end of the week devoted on crustacean.  Lowest prices were on Tuesday and Wednesday, and higher on Monday and Friday.  Banning one day per week would reduce revenues less than a month of seasonal closure.  Banning one day per week would reduce the double effort than a month of closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In experiences undertaken in Alicante, results showed that the losses from banning on Wednesday might be compensated by price increases and reductions of exploitation costs (Samy-Kamal et al, 2015). In case the reductions of fishing effort were not applied in terms of days per week, an alternative option could be decreasing the total number of working hours per day.…”
Section: Bottom Trawl Fisherymentioning
confidence: 99%
“…In experiences undertaken in Alicante, results showed that the losses from banning on Wednesday might be compensated by price increases and reductions of exploitation costs (Samy-Kamal et al, 2015). In case the reductions of fishing effort were not applied in terms of days per week, an alternative option could be decreasing the total number of working hours per day.…”
Section: Bottom Trawl Fisherymentioning
confidence: 99%
“…Many countries are using the Dutch auctions in first sale/wholesale fish markets, including Sidney's Pyrmont in Australia (Hickey, 1989); the Basque Country in Spain (García et al ., 2010); Ancona and Pescara in Italy (Gallegati et al ., 2011; Giulioni & Bucciarelli, 2011); Sete and Lorient in France (Gallegati et al ., 2011; Guillotreau & Jiménez‐Toribio, 2011). The output data of wholesale fish markets from Dutch auctions have been useful in providing a substantial amount of data for many scientific studies with fisheries economic and sustainable management objectives ( e.g ., Fluvia et al ., 2012; Samy‐Kamal et al ., 2014; Samy‐Kamal et al ., 2015a, 2015b, 2015c). These auctions are working using the same mechanisms and technologies in these countries.…”
Section: Discussionmentioning
confidence: 99%
“…Ancona and Pescara in Italy (Gallegati et al, 2011;Giulioni & Bucciarelli, 2011); Sete and Lorient in France (Gallegati et al, 2011;Guillotreau & Jiménez-Toribio, 2011). The output data of wholesale fish markets from Dutch auctions have been useful in providing a substantial amount of data for many scientific studies with fisheries economic and sustainable management objectives (e.g., Fluvia et al, 2012;Samy-Kamal et al, 2014;Samy-Kamal et al, 2015a, 2015b, 2015c.…”
Section: Seasonality Of Prices Abundance Biomass and Revenuementioning
confidence: 99%
“…Concentrating the reduction during a single season can cause price decreases because of the irregular supply of fresh fish to the market (Samy-Kamal et al, 2015b). On the other hand, if effort reductions do not affect the continuous market supply (i.e., reducing 1-2 days per week; Scenarios 6-8), the reduction in the amount of catches over the short term would be balanced by an increase in the market price value because of the elasticity of supply and demand (Macher et al, 2008;Samy-Kamal et al, 2015a). During the medium to long term, the increase in the amount of catches will produce a higher supply to the market that may also affect prices if demand does not increase.…”
Section: Figure 12 |mentioning
confidence: 99%